2016
DOI: 10.3389/fnmol.2016.00122
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Metabolism, the Ketogenic Diet and β-Hydroxybutyrate: Novel Approaches to Adjuvant Brain Tumor Therapy

Abstract: Malignant brain tumors are devastating despite aggressive treatments such as surgical resection, chemotherapy and radiation therapy. The average life expectancy of patients with newly diagnosed glioblastoma is approximately ~18 months. It is clear that increased survival of brain tumor patients requires the design of new therapeutic modalities, especially those that enhance currently available treatments and/or limit tumor growth. One novel therapeutic arena is the metabolic dysregulation that results in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 149 publications
(191 reference statements)
2
74
0
5
Order By: Relevance
“…Thus, these case reports, along with numerous anecdotal observations, presented encouraging signs of metabolic reprogramming by the KD, along with the increased efficacy of standard of care treatment for malignant glioma (23,29). This preliminary evidence of the benefit of KD for cancer therapy is currently being validated in ongoing, controlled clinical trials, which include patients with malignant glioma (25).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, these case reports, along with numerous anecdotal observations, presented encouraging signs of metabolic reprogramming by the KD, along with the increased efficacy of standard of care treatment for malignant glioma (23,29). This preliminary evidence of the benefit of KD for cancer therapy is currently being validated in ongoing, controlled clinical trials, which include patients with malignant glioma (25).…”
Section: Introductionmentioning
confidence: 73%
“…It has been postulated that a ketogenic diet, i.e., a diet consisting of high fat, low carbohydrates and adequate protein, may be useful in the treatment of brain tumors (25)(26)(27)(28)(29)(30)(31). The present study was conducted to assess the therapeutic efficacy and safety of a KD concomitant with intranasal perillyl alcohol as a novel therapeutic strategy for recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While epidemiological associations among obesity, cancer, and ketogenic diets are debated (Liskiewicz et al, 2016; Wright and Simone, 2016), a meta-analysis using ketogenic diets in animal models and in human studies suggested a salutary impact on survival, with benefits prospectively linked to the magnitude of ketosis, time of diet initiation, and tumor location (Klement et al, 2016; Woolf et al, 2016). Treatment of pancreatic cancer cells with ketone bodies ( d -βOHB or AcAc) inhibited growth, proliferation and glycolysis, and a ketogenic diet (81% kcal fat, 18% protein, 1% carbohydrate) reduced in vivo tumor weight, glycemia, and increased muscle and body weight in animals with implanted cancer (Shukla et al, 2014).…”
Section: Ketone Bodies In Cancer Biologymentioning
confidence: 99%
“…In the CT-2A malignant mouse astrocytoma model, a calorie-restricted KD decreased plasma glucose, plasma insulin-like growth factor and tumor weight when administered as a stand-alone therapy and elicited potent synergistic anti-cancer effects when administered in combination with glycolytic inhibitor 2-deoxy- d -glucose (2-DG) [79,80]. In the GL-261 malignant glioma model, KD fed mice had reduced peritumoral edema and tumor microvasculature, 20–30% increased median survival time and achieved complete and long-term remission when used concomitantly with radiation therapy [81,82,83]. A similar synergistic effect was observed between KD and temozolomide in the GL-261 model [84].…”
Section: Kds In the Management Of Adult Malignant Gliomasmentioning
confidence: 99%